PELAKSANAAN LAYANAN KONSELING INDIVIDU DITINJAU DARI MODEL MODEL CONTEXT INPUT PROCESS PRODUCT (CIPP) - Cahyono, Tri (Universitas Borneo Tarakan, 2022)
AbstractGuidance and counseling is held to facilitate the development of students/counselees so that they are able to actualize their potential or achieve optimal development. Guidance and counseling is a component in the entire education system, especially in schools, with guidance and counseling at school a student feels that the teacher is paying attention to the behavior he is doing. Individual counseling is the most influential part of the process of providing service assistance to counselees who need help. This service can be used if the problems faced by the individual are more personal and require several processes which can be carried out by the teacher or psychologist or the parents concerned who will do it. The implementation of individual counseling services in schools is in fact not in accordance with theory, such as counselees who do not have the courage to tell their problems directly, are not in accordance with existing counseling approaches and there is no communicative and healing relationship.Keywords: Individual Counseling, CIPPAbstractBimbingan dan konseling diselenggarakan untuk memfasilitasi perkembangan peserta didik/konseli agar mampu mengaktualisasikan potensi dirinya atau mencapai perkembangan secara optimal. Bimbingan dan konseling menjadi satu komponen dalam keseluruhan sistem pendidikan khususnya di sekolah, dengan adanya bimbingan dan konseling di sekolah seorang siswa merasa bahwa dirinya diperhatikan oleh guru atas tingkah laku yang diperbuatnya. Konseling individual menjadi bagian yang paling berpengaruh terhadap proses pemberian bantuan layanan kepada konseli yang membutuhkan bantuin. Layanan ini dapat digunakan jika permasalahan yang dihadapi individu itu lebih bersifat pribadi dan memerlukan beberapa proses yang mana dapat dilakukan oleh guru atau ahli psikolog atau orang tua yang bersangkutan yang akan melakukannya. Pelaksanaan layanan konseling individu disekolah pada kenyataannya tidak sesuai dengan teori seperti konseli yang belum berani menceritakan permasalahanya secara langsung, tidak sesuai denan pendekatan konseling yang ada dan tidak terjadi hubungan yang komunikatof dan menyembuhkan.Kata Kunci : Konseling Individu, CIPP